(untitled) (Research, Society and Development, 2024)
Introduction: In recent years, the growth of various illnesses has been highlighted, resulting in an increase in demand for help from healthcare professionals, leading to overcrowding in healthcare environments. Home care is a sustainable way to care for patients, thus avoiding overcrowding in healthcare environments. Objective: The present study aimed to highlight the role of the pharmacist within home care activities, through the analysis of articles that demonstrate the participation of this health professional in home care. Methodology: The methodology used in the study is systematic review. A quantitative and qualitative analysis of articles was carried out, highlighting the role of the pharmacist in home care carried out in different countries. Results and discussion: The role of the pharmacist in home care carried out in different countries highlights the contribution in different areas, such as pharmacotherapy, pharmacoeconomics, pharmacovigilance and health education. In addition to the notable contribution in the areas mentioned, professionals from other health areas and patients demonstrated satisfaction with the pharmacist’s assistance in home care. Conclusion: The integration of the pharmacist in home care appears to be positive due to the benefits in the treatment of patients, such as more effective and safe medication treatment, due to the pharmacist’s contribution in relation to medications and non-pharmacological guidance.